Large-scale effects of national policy assessment on the political and pedagogical management of schools of Porto Alegre: Exploring relationships and uses - Ghisleni, Ana Cristina; Luce, Maria Beatriz (Education Policy Analysis Archives, 2016)
This article presents an analysis of the relationships established by school system administrators and teachers (principals and classroom staff) with the national evaluation policy and how they use this type of assessment. By confronting the positions of the two groups, whose speeches were codified through the N-Vivo 10 software, a set of quantitative and qualitative analyses are drawn. The notion of recontextualization offered by Bernstein (1998, 2003) and the contributions of Dias Sobrinho (1996, 2008) reinforce the understanding of the assessment’s political dimension that goes beyond the limits of performance and measurement. The research design favors the confrontation of positions, interests, emphasis and differentiated appropriations concerning the concepts, instruments, and results of high stakes evaluation. It also shows that diverse understandings concerning the policy result in a precarious and insufficient use of the external evaluation proposal.